The Use of Cognition by Amphibians Confronting Environmental Change: Examples from the Behavioral Ecology of Crawfish Frogs (Rana areolata) - Michael J. Lannoo; Rochelle M. Stiles (Animals)
Amphibian conservation concerns frequently center on the idea of ‘saving’ them, with the underlying assumption they are the passive victims of anthropogenic environmental change. But this approach ignores the physiological, biochemical, and behavioral flexibility amphibians have employed since they first evolved ~365 million years ago. One overlooked advantage amphibians possess in the struggle for survival, and one humans might use in their efforts to conserve them, is their brains share the same blueprint as human brains, which allows them to acquire knowledge and understanding through experiences—in other words, amphibians have cognitive capabilities that assist them in their effort to survive. Here, we use four examples from our work on the behavioral ecology of Crawfish Frogs (Rana areolata) to form hypotheses about how cognition affects amphibian reaction to environmental and social change. The first two examples describe Crawfish Frog responses to seasonality and reproductive status, the third details their reaction to ecological disturbance, and the fourth describes how their response to the same stimulus changes with growth/age. In each example, we detail the neuronal circuitry thought to be involved and hypothesize the role of cognition. We propose that as one component of our fight to conserve amphibians, researchers should consider the full range of anatomical, physiological, biochemical, and behavioral features amphibians themselves employ in their defense, which are features responsible for their historical evolutionary success up until the Anthropocene. Further, we submit that acknowledging amphibians possess cognitive abilities can enrich interpretations of not only behavioral and ecological observations but also of neuroanatomical and neurophysiological results.